Production of 1−+ exotic charmonium-like states in electron-positron collisions - Xiao-Yu Zhang; Pan-Pan Shi; Feng-Kun Guo (Physics Letters B)
The absence of observed charmonium-like states with the exotic quantum numbers JPC=1−+ has prompted us to investigate the production rates of the 1−+ DD‾1(2420) and D⁎D‾1(2420) hadronic molecules, which we refer to as ηc1 and ηc1′, respectively, in electron-positron collisions. Assuming a hadronic molecular nature for the vector charmonium-like states ψ(4360) and ψ(4415), we evaluate the radiative decay widths of ψ(4360)→γηc1 and ψ(4415)→γηc1′. Using these decay widths, we estimate the cross sections for producing ηc1 and ηc1′ in electron-positron annihilations, as well as the event numbers at the planned Super τ-Charm Facility. Our results suggest that the ideal energy region for observing these states is around 4.44 and 4.50 GeV, just above the D⁎D‾1(2420) and D⁎D‾2⁎(2460) thresholds, respectively.